JavaScript in action : 3 fun interactive JavaScript projects - Svekis, Laurence (Packt Publishing, 2019)
"Explore how you can build interactive and dynamic web content using JavaScript to create fun mini projects. No libraries, no shortcuts just learning JavaScript making it DYNAMIC and INTERACTIVE web application. Step by step learning with all steps included. Beginner JavaScript knowledge is required as the course covers only JavaScript relevant to the building of the game. Also, HTML and CSS knowledge is essential as the scope of this course is all JavaScript-focused. Try it now you have nothing to lose. Start building your own version of the game today!"--Resource description page